Strategi Pengembangan Wisata Desa Yang Berkelanjutan - Sukaris Sukaris; Aries Kurniawan; Moh. Dian Kurniawan (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2023)
Background–Currently, tourism potential in Indonesia has considerable potential and opportunity to be developed, especially village tourism owned by villages in Indonesia. Likewise, the village has been able to capture village tourism opportunities that can be developed based on local resources owned, both tourist attractions, culture and other local wisdom. However, not many villages develop it sustainably. Aim – The objectives of this study specifically will examine how the strategies that can be carried out by villages (village tourism managers) in developing village tourism to be sustainable. Design / methodology / approach – The research method used in this study is a qualitative approach where data is collected from informants through focus group discussions. Findings – The results of the study indicate that villages in Gresik Regency are actively developing village tourism, which is marked by the concern of tourism awareness groups (POKDARWIS), as well as the increasing number of developed village tourism destinations. Strategies that can be carried out in developing sustainable tourism villages include optimizing local resources, community involvement, adhering to the planned master plan, managing internally sourced funding, strengthening institutions, making village tourism development a priority, increasing the ability to sell village tourism products. supported by competent human resources that meet excellent service standards and the motivation for continuous development to do new things. Research implication Theoretical implications; In future studies, it is necessary to have a study that connects the concept of halal tourism with sustainability, especially in Gresik Regency, which is known as the city of santri. Limitations – This research is mostly digging data from tourism managers (POKDARWIS), so it does not involve visitors and other stakeholders.